Association of Immune Cell Subtypes and Phenotype With Subsequent Invasive Candidiasis in Patients With Abdominal Sepsis. Issue 2 (August 2019) - Arens, Christoph; Kramm, Timo; Decker, Sebastian; Spannenberger, Jens; Brenner, Thorsten; Richter, Daniel Christoph; Weigand, Markus Alexander; Uhle, Florian; Lichtenstern, Christoph
ABSTRACT: Background: In nonneutropenic intensive care unit (ICU) patients, current risk stratification scores lack specificity to reliably predict the risk of a prospective invasive candidiasis (IC). We aimed to explore possible associations of distinct immunological markers with different degrees of Candida affection in patients with abdominal sepsis. Methods: The presented explorative, noninterventional diagnosis study recruited patients admitted to the surgical ICU at Heidelberg University Hospital with abdominal sepsis. Over 5 days, we determined white blood cell count, 1, 3-β-D-glucan, and HLA-DR expression; the amount of Th1, Th17, regulatory T, T helper, and cytotoxic T cells; Dectin-1 and TLR2-expression; the amount of T, B, and NK cells; the ex vivo secretion of IL-8 upon stimulation with LPS, flagellin, and zymosan; and the distribution of distinct T-cell cytokines in a daily manner. On day 21, patients' Candida infection status was stratified in no colonization or IC, colonization or IC. Results: A total of 26 patients were included. On day 21, five patients showed no colonization or IC, in 13 patients a colonization was detected, and eight patients were diagnosed with IC. On study inclusion, the stratification groups showed comparable values in standard laboratory parameters and morbidity scores. Decreased B and NK cell counts, as well as reduced IL-8 secretion after ex vivo stimulation with LPS or flagellin seemed to be associated with a higher risk of subsequent Candida colonization. Even lower values could distinguish the therapy-relevant difference between prospective IC from colonization alone. Conclusions: We were able to show distinct immune system impairments in early abdominal sepsis by specific immune-based measurements. A possible association of these impairments with a subsequent Candida affection is shown. Abstract : Supplemental Digital Content is available in the text